The Effectiveness of Spiritual Emotional Transcedence Care (SET Care ) On Stress Levels of Pulmonary Tuberculosis Patients: A Quasi-Experimental Study - Hartono, Hartono; Kusnanto, Kusnanto; Wahyuni, Erna Dwi (Critical Medical and Surgical Nursing Journal, 2025)
Introduction: Tuberculosis (TB) is a chronic infectious disease that can affect various organs and often leads to psychological stress. Spiritual Emotional Transcendence Care (SET Care), which integrates the SEFT approach with self-transcendence theory, is a relaxation technique aimed at reducing stress in TB patients.  Methods: This quasi-experimental study used a non-randomized pretest-posttest control group design. A total of 20 pulmonary TB patients were selected through purposive sampling and divided into treatment (n=10) and control (n=10) groups. Stress levels were measured using a modified DASS-42 stress subscale. Data were analyzed using the Wilcoxon signed-rank test and the Mann-Whitney U test with a significance level of p ≤ 0.05. Results: Demographic data showed equal gender distribution (50% male, 50% female), with most participants aged 44–55 years and educated up to senior high school. A significant reduction in stress levels was found in the treatment group after the intervention (p = 0.004), while the control group showed no significant change (p = 0.655). The Mann-Whitney U test confirmed a significant difference in post-test scores between groups (p = 0.000). Conclusions: SET Care effectively reduces stress in pulmonary TB patients and can be considered a complementary nursing intervention. Its integration into nursing practice supports holistic care by addressing emotional and spiritual well-being, potentially enhancing treatment adherence and patient outcomes.